Flexible impulse response of the multi-bar linkage with heavy load - Feng Xianzhang; Cheng Junwei; Cui Yanmei; Jiang Zhiqiang (Functional Materials, 2016)
It is based on the advantages of virtual prototyping technology, the dynamics mathematic model was established for the large mechanism by applying multi body dynamics theory. In order to adapt the users to special request of the strip width size, appeared the continuous casting and continuous rolling technology, and greatly reduce the width types of continuous casting. The components of the equipments are often considered the rigid body. The precision is not high premise in the process of work, usually the parts works as elastic under the high speed and the heavy load, neglects various components the elastic function will cause the result error, even will be wrong. Studied analysis dynamic characteristic of the adjustment width machine, and analyzed the component in detail for the rigid body or the elastic. The results provide the theoretically support to work out adjustment the width potentialities and strength analysis of the key parts.